2020
DOI: 10.1177/0886260520980386
|View full text |Cite
|
Sign up to set email alerts
|

A Socio-ecological Framework for Understanding Workplace Violence in China’s Health Sector: A Qualitative Analysis of Health Workers' Responses to an Open-ended Survey Question

Abstract: Workplace violence (WPV) in the health sector is a global public health issue. The magnitude of WPV is a particular concern in China’s health system. To examine the potential causes of WPV, we analyzed 3,045 qualitative responses to an open-ended question in a survey with health workers in the Zhejiang province, China. We adapted a four-level socio-ecological framework (societal/systemic, community/organizational, interpersonal, and individual) to thematically analyze the data. Ten sub-themes emerged. Within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…In our study, inconsistent with previous studies, 2 8 we found that both front-line/non-front-line HCWs with higher professional titles were more likely to suffer from WPV. The association between professional titles and WPV may be triggered by the differences in the patients they treated.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, inconsistent with previous studies, 2 8 we found that both front-line/non-front-line HCWs with higher professional titles were more likely to suffer from WPV. The association between professional titles and WPV may be triggered by the differences in the patients they treated.…”
Section: Discussioncontrasting
confidence: 99%
“…In the UK, over a decade of austerity and vast public spending cuts to health and social care services have led to an overburdened health system and chronic staff shortages [29, 30]. Other societal factors include social and cultural norms that condone violence such as accepting workplace violence in healthcare as being an unfortunate but inevitable “part of the job” [31, 32].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Risk factors for violence exposure at the institutional level include insufficient support from organisational leaders and a lack of violence prevention policy, education and program evaluation [31]. At the interpersonal level, personal relationships and social interactions influence the risks of becoming a victim or perpetrator of violence and include poor communication and distrust between healthcare practitioners and patients, and bullying behaviours between colleagues [31].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 18 , 19 Specifically, Chinese legislation about workplace violence has weakness, like the absence of legislation on workplace violence and the ineffective enforcement authorities. 20 - 22 The continuance of workplace violence in the hospitals has violated the Chinese law. Therefore, the effectiveness of China’s health legislation and policy needs to be assessed.…”
Section: Introductionmentioning
confidence: 99%